2012
DOI: 10.1186/1475-2840-11-74
|View full text |Cite
|
Sign up to set email alerts
|

High fat diet-induced glucose intolerance impairs myocardial function, but not myocardial perfusion during hyperaemia: a pilot study

Abstract: BackgroundGlucose intolerance is a major health problem and is associated with increased risk of progression to type 2 diabetes mellitus and cardiovascular disease. However, whether glucose intolerance is related to impaired myocardial perfusion is not known. The purpose of the present study was to study the effect of diet-induced glucose intolerance on myocardial function and perfusion during baseline and pharmacological induced hyperaemia.MethodsMale Wistar rats were randomly exposed to a high fat diet (HFD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 17 publications
3
23
0
Order By: Relevance
“…Indeed, the ex vivo cardiac mechanical function was reduced by the HF diet, following the elevated adiposity of the animals irrespective of their body weight. That observation has already been presented in the literature after a HF diet period [9,31], after weight gain through post-natal overfeeding in the mouse [7] and in the rat [8] as well as in the ZDF rat [6]. This depressed ex vivo cardiac mechanical activity observed in this study could be related to changes in the cardiac metabolism related to the whole body glucose intolerance, the increased degree of saturation of the cardiac membranes as shown by the increase in the SFAs at the detriment of MUFAs [36] and the pro-inflammatory environment as indicated by the low ratio EPA/AA that predisposes to a balance of eicosanoids favoring platelet aggregation and inflammatory signaling [37,38].…”
Section: Discussionsupporting
confidence: 61%
“…Indeed, the ex vivo cardiac mechanical function was reduced by the HF diet, following the elevated adiposity of the animals irrespective of their body weight. That observation has already been presented in the literature after a HF diet period [9,31], after weight gain through post-natal overfeeding in the mouse [7] and in the rat [8] as well as in the ZDF rat [6]. This depressed ex vivo cardiac mechanical activity observed in this study could be related to changes in the cardiac metabolism related to the whole body glucose intolerance, the increased degree of saturation of the cardiac membranes as shown by the increase in the SFAs at the detriment of MUFAs [36] and the pro-inflammatory environment as indicated by the low ratio EPA/AA that predisposes to a balance of eicosanoids favoring platelet aggregation and inflammatory signaling [37,38].…”
Section: Discussionsupporting
confidence: 61%
“…Diet-induced obesity is associated with dyslipidemia, glucose intolerance and insulin resistance in rats [ 25 , 40 42 ]. In the present study, 6 weeks of HFD led to a marked increase in abdominal fat depots and a rise in serum total cholesterol levels, but not in a rise of serum triglyceride, insulin or glucose levels as measured under non-fasting conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, at baseline the rate of LV volume change across the cardiac cycle (dV/dt) tended to be increased for HFD rats in both systole and diastole suggesting that, if anything, baseline cardiac function is enhanced, rather than reduced, after 6 weeks of HFD. In literature inconsistent findings have been reported as far as the effect of HFD on myocardial function is concerned, with some studies reporting reduced function [ 25 , 46 ], unchanged function [ 42 ] and improved function [ 21 ], respectively. In this context it is of note that one study reported that functional outcome was dependent on the exact composition of the HFD diet [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the metabolic undisturbed heart usually responds to injury by increasing myocardial glucose metabolism [22,24], this adaptive response is inhibited by insulin resistance, which is a characteristic of obesity and T2DM. This inhibition results in increased myocardial fatty acid metabolism [31,32], increased oxygen consumption, decreased cardiac efficiency [31] and altered myocardial perfusion [33]. In obese or T2DM animals subjected to myocardial ischaemia the findings are inconclusive.…”
Section: Myocardial Substrate Metabolismmentioning
confidence: 99%